Public Service Innovation Towards Smart Villages: Between Expectation and Realisation in Melikan Village - Andi Masrich; Adji Suradji Muhammad; Sucahyo Heriningsih; Ahmad Mustanir; Suharto Suharto; Eka Suswaini (Jurnal Manajemen Pelayanan Publik, 2023)
The idea of a smart village encompasses various aspects of rural life in the modern digital era, with a key focus on information technology infrastructure. The aim of this study is to explore the hopes and requirements of rural residents and assess the level of preparedness of village authorities to leverage technological advancements towards creating smart villages. The research method used is the qualitative research method. The research was conducted in Melikan Village, Klaten Regency, Central Java. The research used several main data sources: village officials and the Melikan Village community. The data collection techniques used were interviews, observation, and FGD. The results show that information and communication technology is vital for the Melikan Village community, but the village government is not yet sufficiently prepared to fulfil the community's expectations. The village government is encouraged to collaborate and be creative with parties that can develop digital services. Community empowerment can technically be done by using application software or websites to open up opportunities for information channelling and support overall rural development. However, the successful implementation of smart villages is highly dependent on the motivation of village leaders, active community participation, and potential village resources. The implication of this research is that the Melikan Village government needs to immediately overcome the obstacles that hinder the adoption of innovations in government services towards smart villages.